Forensic Problems in Detrmining out the Cause of the Death in Old People that Have Passed Away Under Unclear Circumstances - Susło, Robert; Siuta, Jędrzej; Trnka, Jakub; Gęsicki, Marcin; Drobnik, Jarosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
An analysis have been performed of the autopsies performed in the years 2008–2009 at the Forensic Medicine Department, Medical University, Wroclaw, Poland to choose the death cases of people aged 60 years and above. Using the results of the review of the literature and the autopsy reports 4 main groups of problems influencing the forensic practitioners work, pertaining the old people, have been identified: loneliness and isolation resulting in quite a big delay in finding out corpses and advanced post-mortem changes at the time of autopsy, old people susceptibility to serious injuries resulting from even minor trauma, coexisting advanced chronic diseases complicating the decision whether or not they constituted a real cause of death and susceptibility of the old people corpses to post-mortem changes. It has been successfully connected to the forensic autopsy results. The abovementioned issues constitute the specific problems in forensic opinion giving in cases of the old people deaths. The high incidence of various level alcohol intoxication in old people who died because of various causes suggests that the problem of alcohol abuse in this age group may be of quite a big importance.